[This memorandum will serve as an invoice for the services of Urban Resources in Northeast area for the period described June 1992 8 333 00] (Tufts Archival Research Center, 2007)
Memo containing the April report. Discusses the issues of privacy, taxes and those to be concerned about, in different states. Contains a summary of the activities of decemeber and january which include meetings with labor union representatives to develop their role in the LMC.